2019
DOI: 10.5430/wje.v9n1p20
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Loneliness Levels and Digital Game Addiction of Middle School Students According to Various Variables

Abstract: The aim of this study was to examine the loneliness levels of students at the middle school level and their digitalgame addictions in terms of various variables. The study group consisted of 404 volunteer students in 5th-8th gradein Kutahya, Turkey. As data collection tools, "Digital Game Addiction Scale", developed by Lemmens et al. (2009)and "UCLA Loneliness Scale" developed by Russell et al. (1980) were used. The SPSS package program was usedfor the analysis of the data. According to research findings, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
(22 reference statements)
3
7
1
2
Order By: Relevance
“…It was thought that the reason for this situation may be due to the fact that the elderly students use their leisure more consciously and efficiently as their sense of responsibility increases. On the other hand, there are studies in the literature that do not support the same results as this study (Ekinci et al, 2019). This is due to the fact that the sample groups are different.…”
Section: Discussioncontrasting
confidence: 73%
“…It was thought that the reason for this situation may be due to the fact that the elderly students use their leisure more consciously and efficiently as their sense of responsibility increases. On the other hand, there are studies in the literature that do not support the same results as this study (Ekinci et al, 2019). This is due to the fact that the sample groups are different.…”
Section: Discussioncontrasting
confidence: 73%
“…It was found that gaming disorder level is positively associated with age and class. When the literature was reviewed, found similar results were found [ 1 , 105 , 106 , 107 , 108 , 109 ]. As the age and class level increase, children’s awareness of life and possible problems will also increase.…”
Section: Discussionsupporting
confidence: 59%
“…The most important of these quests is to evaluate the time of individuals by doing sports activities. Many studies have reported that leisure activities are essential for sports activities (Escaron et al, 2019;Ayhan et al, 2018;Ekinci et al, 2019;Berlin et al, 2018). The adaptation of people to changes in the increase of leisure time, simplifying their lives, extending their life span and made more significant contributions to increase their enjoyment of life by giving them more time (Mansuroğlu, 2002).…”
Section: Introductionmentioning
confidence: 99%